2010
DOI: 10.1097/maj.0b013e3181ca43fe
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypoglycemia With Mortality for Subjects Hospitalized With Pneumonia

Abstract: Background Prior research has shown that hypoglycemia is associated with worse outcomes for the elderly, in sepsis, and in children with pneumonia. The purpose of this study was to examine whether hypoglycemia (< 70 mg/dL) is associated with increased 30-day mortality, after adjusting for potential confounders, for adults hospitalized with pneumonia. Methods A retrospective cohort study conducted at two tertiary teaching hospitals. Eligible subjects were admitted with a diagnosis of, and had a chest x-ray co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
13
1
1
Order By: Relevance
“…Most of these hypoglycemic episodes were treatment related, but spontaneous hypoglycemia is also known to be frequent (1). Hypoglycemia is associated with increased mortality (26). However, a cause and effect relationship between hypoglycemia and mortality has not been established (5).…”
mentioning
confidence: 99%
“…Most of these hypoglycemic episodes were treatment related, but spontaneous hypoglycemia is also known to be frequent (1). Hypoglycemia is associated with increased mortality (26). However, a cause and effect relationship between hypoglycemia and mortality has not been established (5).…”
mentioning
confidence: 99%
“…25,38,39,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Hypoglycemia could be partly responsible for the adverse effects noted with intensive insulin therapy, including mortality. 25 A large retrospective analysis of hypoglycemia in ICUs showed a stepwise and significant increase in mortality with increasingly severe hypoglycemia.…”
Section: Grade: Strongmentioning
confidence: 99%
“…Furthermore, functional status prior to hospitalization had an even greater impact than comorbidities, 8 and it also had an influence after discharge. On the other hand, some studies related to the prediction of mortality in infection or sepsis have found that many laboratory variables are linked to an adverse prognosis, such as thrombocytopenia and thrombocytosis, 9 abnormal WBC count with increased band form percentage, 12,21 low cholesterol and albumin levels, 10,11 abnormal glucose level, 12,16,17 and high values of blood urea nitrogen, creatinine, and total bilirubin. 12,13 Nevertheless, those hospital-based surveys were only applicable to the general population and usually specific to one kind of infection or sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…8 As to infection-related deaths, unstable vital signs, preexisting terminal illness, and abnormal platelet count have been reported to increase the risk of mortality. 5,9 Several studies have also reported that age, comorbidity, nutrition status, the number of organ dysfunctions, 10e15 and abnormal glucose level 16,17 are the most important predictors for hospital mortality in patients with infection or sepsis; however, these studies were not geriatric specific.…”
Section: Introductionmentioning
confidence: 98%